Effect of Oil and Gas Exploration on Land Ownership in Uganda: A Case Study of Buliisa District - Godwin Kule (Uganda Christian University, 2024)
Uganda's recent discovery of oil reserves in the western region has sparked both excitement and concerns. While the potential economic benefits are undeniable, understanding effects of oil and gas exploration activities on the landownership is crucial. This study delves into the case of Buliisa District, situated at the heart of this unfolding story. By examining the effects of oil and gas exploration activities on the land ownership, we aim to shed light on the complex realities unfolding in Buliisa and contribute to informed decision-making about the future of oil development in Uganda.
Undergraduate research